BCL-1 rearrangements and p53 mutations in atypical chronic lymphocytic leukemia with t(11;14)(q13;q32) - C De Angeli; D Gandini; A Cuneo; S Moretti; R Bigoni; MG Roberti; A Bardi; GL Castoldi; L del Senno (Haematologica, 2000)
BACKGROUND AND OBJECTIVES: The translocation t(11;14) (q13;q32), typically described in mantle cell lymphomas (MCL), has also been found in some cases of non-MCL lymphoproliferative disorders, such as splenic lymphoma with villous lymphocytes (SLVL), multiple myeloma (MM), prolymphocytic leukemia (PLL), typical and atypical chronic lymphocytic leukemia (CLL and aCLL). In order to define better the genetic features of aCLL with t(11;14), which could represent a distinct disease subset, we looked for genetic lesions in the BCL-1 locus and in BCL-2, BCL-6, c-myc and p53 genes. DESIGN AND METHODS: We investigated a panel of B-lymphoproliferative disorders with translocation t(11;14)(q13;q32) including nine aCLL, six MCL and one MM. Southern and Northern blot analysis was used to investigate DNA structure and RNA expression; SSCP and direct sequencing were used to detect and characterize p53 point mutations; cytofluorimetric analysis was used to quantify p53 protein. RESULTS: Alterations of BCL-2, BCL-6 and c-myc were not detected. Conversely, BCL-1 rearrangements were present in 4 out of 7 aCLL and in 2 out of 4 MCL. A high incidence of p53 gene alterations was found, almost equivalent in aCLL and MCL. INTERPRETATION AND CONCLUSIONS: Our results indicate that the occurrence of BCL-1 locus lesions in aCLL selected for t(11;14) is as high as in MCL. Interestingly, rearrangements in the mTC1 (minor translocation cluster 1) were only found in aCLL. Therefore, the two B-cell chronic lymphoproliferative disorders share similar molecular rearrangements and the t(11;14) identifies a subset of B-CLL sharing molecular features with MCL and characterized by aggressive clinical evolution.